PUPUK MULTINUTRIENT BERBASIS GEL DARI LIMBAH MONOKULTUR PROSES FERMENTASI - Oktavian, Dio Ajeng; Iswono, Veronica Putri; Dinnastyar, Faishal Ahmad; Marsen, Vinsen Alexander; Retnowati, Dewi; Anggorowati, Dwi Ana; Rahman, Nanik Astuti (jurnal ATMOSPHERE, 2023)
Gel organic fertilizer is the result of liquid organic fertilizer that is converted from liquid to gel, which is produced naturally. This gel organic fertilizer is an additional material used to meet the nutrient needs of plants to increase better productivity. The source of gel organic fertilizer is not much different from liquid organic fertilizer. Where the material for making gel organic fertilizer can be obtained from agricultural residues, MSME industries, factory waste that has no selling value such as vegetable waste, cheese whey waste, and molasses. This study aims to determine the effect of variable thickening agents on gel fertilizer from various gel structure modifiers. The treatments are as follows: The fixed variable is the fermentation time of 14 days and the independent variable of gel structure modifiers including tapioca starch, Carbopol 94, and Aquakeeper Hydrogel. The results of this research show that the treatment of free variables has a very significant effect and gives the best results without involving auxiliary media such as heating.